2018
DOI: 10.1101/389668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hexokinase: A central player in the synergism of high-intensity intermittent exercise and every-other-day intermittent fasting regimen on energy metabolism adaptations

Abstract: 2Visceral lipid accumulation, organ hypertrophy and a reduction in skeletal muscle 3 strength are all signs associated with the severity of obesity related disease. Intermittent 4 fasting (IF) and high-intensity intermittent exercise (HIIE) are natural strategies that, 5 individually, can prevent and ameliorate obesity along with metabolic syndrome and its 6 associated diseases. However, the combinatorial effect of IF and HIIF on energetic 7 metabolism is currently not well understood. We hypothesized that the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Research by Kotarsky et al, (2021) also reported that aerobic exercise while fasting has been proven to stimulate fat dismantling when glycogen reserves are depleted, thus having an impact on reducing inflammatory risk factors as indicated by a decrease in CRP. Bosco et al, (2021) reported that mobilization and the use of fatty acids in adipocytes increase calorie expenditure, which can prevent the risk of inflammation in obesity, and Real-Hohn et al, (2018) stated that weight loss after exercising while fasting positively influences the state of inflammation through reducing adipose tissue and expression. CRP gene in adipocytes and macrophages significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Kotarsky et al, (2021) also reported that aerobic exercise while fasting has been proven to stimulate fat dismantling when glycogen reserves are depleted, thus having an impact on reducing inflammatory risk factors as indicated by a decrease in CRP. Bosco et al, (2021) reported that mobilization and the use of fatty acids in adipocytes increase calorie expenditure, which can prevent the risk of inflammation in obesity, and Real-Hohn et al, (2018) stated that weight loss after exercising while fasting positively influences the state of inflammation through reducing adipose tissue and expression. CRP gene in adipocytes and macrophages significantly.…”
Section: Discussionmentioning
confidence: 99%